Tinjauan Fiqh Siyasah Tanfidziyah Terhadap Implementasi Peraturan Pemerintah Nomor 11 Tahun 2021 Tentang Badan Usaha Milik Desa - Anggraini, Putri; Nur, Efa Rodiah; Mu'in, Fathul (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2025)
The purpose of this study is to understand the “Review of Fiqh Siyasah Tanfidziyah on the Implementation of Government Regulation No. 11 of 2021 concerning Village-Owned Enterprises at BUMDes Abdi Tani, Rejosari Jaya Village, Belitang Jaya District, East Oku Regency.” This research technique employs a qualitative and descriptive approach. This research data comes from primary data obtained through interviews with Rejosari Jaya Village Government Apparatus and documents related to BUMDes management and secondary data obtained by researchers through relevant literature review. The findings of this research reveal that the administration of BUMDes in Rejosari Jaya Village does not completely comply with Government Regulation No. 11 of 2021 regarding “BUMDes”. This is due to the lack of ability of administrators and village government officials in managing BUMDes. For this reason, training and coaching are needed to improve the ability of the management to manage BUMDes Abdi Tani. Fiqh Siyasah Tanfidziyah review of government regulation No. 11 of 2021 concerning Village-Owned Enterprises (BUMDes). That the Village-Owned Enterprises are the implementers of Siyasah Tanfidziyah, the management of Village-Owned Enterprises has not gone well because the management lacks responsibility and mandate in managing BUMDes abdi tani, this is in accordance with the letter al-anfal verse 27 which explains the responsibility and mandate of the Bumdes Abdi Tani implementer.